Victims and Insights: Voices of Children on Road Traffic Accidents - Kharel, Krishna (Annual Oxford Journal, 2025)
Road traffic accidents are a serious public health issue worldwide, particularly affecting children and young adults. This qualitative case study aimed to explore the human-related causes of road traffic accidents among students in Butwal Sub-Metropolitan City, Nepal, based on the lived experiences and perceptions of injured children and their parents. Participants were selected using criterion based purposive sampling, focusing on school going children who were recorded as road traffic accident victims in the area police office. Data were collected through in-depth interviews with students and semi-structured interviews with their parents, and field observations and data were analyzed by using the thematic analysis process. The study identified key behavioral factors contributing to road traffic accidents, including high-speed driving, pedestrian negligence, lack of parental awareness, and carelessness of vehicle riders. Results show that speeding in school zones, unsafe pedestrian practices, and inadequate parental guidance significantly increase students’ vulnerability to road traffic accidents. Human behaviors are compounded by insufficient road safety education and weak enforcement of traffic rules. The results align with existing national and global studies, underscoring that most road traffic accidents are preventable and primarily linked to human error. It concludes that reducing road traffic accidents requires a multi-sectoral approach, including stronger traffic law enforcement, public awareness campaigns, improved urban planning and active parental involvement.